2020
DOI: 10.1002/jwmg.21942
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Discord and the Importance of Scale in Scientific Inquiry

Abstract: Scale is widely recognized today as an important concept in ecology because the scale of investigation determines the patterns and processes that can be observed. Ecological investigations can produce different outcomes depending on the scale at which observations are made, and ecological disagreements have occurred simply because investigators addressed the same question using different scales. Here I draw on quail research to illustrate the importance of scale in ecological studies and how lack of scale cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…There is an increasing recognition that resource use occurs in flux with phenology of exploited biotic resources, physiological development of the exploiting species, abiotic conditions, and many other spatially and temporally variable factors (Rettie & Messier, 2000; Sinnott et al., 2021; Tsalyuk et al., 2019; Van der Merwe & Marshal, 2012). Studies without context of temporal and spatial scales may give rise to vastly opposing interpretations of resource use (Hernández, 2020; Hobbs, 2003). Accordingly, the processes of selection for a given species require research across multiple scales and regions to describe disparate behavior under varying conditions which in turn governs locally relevant management practices (Kauffman et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing recognition that resource use occurs in flux with phenology of exploited biotic resources, physiological development of the exploiting species, abiotic conditions, and many other spatially and temporally variable factors (Rettie & Messier, 2000; Sinnott et al., 2021; Tsalyuk et al., 2019; Van der Merwe & Marshal, 2012). Studies without context of temporal and spatial scales may give rise to vastly opposing interpretations of resource use (Hernández, 2020; Hobbs, 2003). Accordingly, the processes of selection for a given species require research across multiple scales and regions to describe disparate behavior under varying conditions which in turn governs locally relevant management practices (Kauffman et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…That is, rainfall may be exerting a strong influence on regional abundance—elevating or depressing abundance at broad spatial extents—while local abundance may vary spatially within these general bounds as local factors (of which rainfall is 1) change across space. Such a proposed hierarchical framework for understanding the influence of rainfall on bobwhite populations in semiarid environments (Hernández 2020) is similar to that proposed for other systems, whereby coarse‐grain patterns constrain fine‐scale processes, but variability at the fine scale is influenced by factors operating at this fine scale plus those operating at the coarse scale (Sala et al 1988, Fuhlendorf et al 2017).…”
Section: Discussionmentioning
confidence: 72%
“…We observed that rainfall at the site level explained considerably less (<10%) of the variation in bobwhite density than past studies have documented for rainfall at a regional level. Recently, Hernández (2020) suggested that the influence of rainfall on bobwhite abundance may decrease with decreasing spatial extent based on hierarchy theory (Allen and Star 1982). Hierarchy theory proposes that systems are structured in nested levels that result in a constraint envelope, whereby the dynamics of an ecological system operate within the limitations imposed by the environmental limits of higher levels and the biotic potential of lower levels (O'Neill et al 1989, Wu 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levin (1992), and most recently Hernandez (2020), have noted that space, time, community structure, and function are critically important to understanding ecological processes. Coupled with biological diversity, those elements necessitate that investigators explicitly state the temporal and spatial scales that were operative during their research.…”
Section: What Scales Are Considered?mentioning
confidence: 99%